2017
DOI: 10.1002/ecs2.2019
|View full text |Cite
|
Sign up to set email alerts
|

Previous burns and topography limit and reinforce fire severity in a large wildfire

Abstract: Abstract. In fire-prone forests, self-reinforcing fire behavior may generate a mosaic of vegetation types and structures. In forests long subject to fire exclusion, such feedbacks may result in forest loss when surface and canopy fuel accumulations lead to unusually severe fires. We examined drivers of fire severity in one large (>1000 km 2 ) wildfire in the western United States, the Rim Fire in the Sierra Nevada, California, and how it was influenced by severity of 21 previous fires to examine the influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 91 publications
3
51
0
Order By: Relevance
“…Prescribed fire is generally considered to be the most effective way to reduce the likelihood of high-severity fire in combination with mechanical treatments (Stephens et al 2009). The 2013 Rim Fire in the Sierra Nevada, California, USA, burned with low severity in areas previously treated with prescribed fires, suggesting that prescribed burning was an effective management tool to reduce fire severity (Harris and Taylor 2017). Many fire-prone forests will require active management to restore ecosystem function, but no single prescription will be appropriate for all areas and, in some portions of the forests, minimal maintenance may be more sustainable in the long term .…”
Section: Discussionmentioning
confidence: 99%
“…Prescribed fire is generally considered to be the most effective way to reduce the likelihood of high-severity fire in combination with mechanical treatments (Stephens et al 2009). The 2013 Rim Fire in the Sierra Nevada, California, USA, burned with low severity in areas previously treated with prescribed fires, suggesting that prescribed burning was an effective management tool to reduce fire severity (Harris and Taylor 2017). Many fire-prone forests will require active management to restore ecosystem function, but no single prescription will be appropriate for all areas and, in some portions of the forests, minimal maintenance may be more sustainable in the long term .…”
Section: Discussionmentioning
confidence: 99%
“…() draw similar conclusions in the context of the Rim Fire, concluding strong prefrontal surface winds aligned with terrain drove some periods of extreme fire spread. Similarly, studies have used statistical analyses to identify environmental factors related to observed degrees of severity, such as the severity of previous burns and topographic slope (Harris and Taylor ) and, for the Rim Fire, the influence of forest structure, fire history, topographic, and weather conditions (Lyderson et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Brotak and Reifsnyder (1977) identify synoptic conditions associated with large fires, chiefly strong prefrontal surface winds preceding a trough, while Peterson et al (2015a) draw similar conclusions in the context of the Rim Fire, concluding strong prefrontal surface winds aligned with terrain drove some periods of extreme fire spread. Similarly, studies have used statistical analyses to identify environmental factors related to observed degrees of severity, such as the severity of previous burns and topographic slope (Harris and Taylor 2017) and, for the Rim Fire, the influence of forest structure, fire history, topographic, and weather conditions (Lyderson et al 2014). The latter study indicated that on days characterized by strong plume activity, severity was moderate to severe regardless of forest conditions.…”
Section: Introductionmentioning
confidence: 99%
“…, van Wagtendonk et al. , Harris and Taylor ), with most only having one response fire, and occurring mostly in conifer forests. These studies have consistently found that fires reburn at the same or higher severity as the previous fire, supporting the idea of a positive feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the effect of the severity of previous fires on the severity of subsequent fire. The handful of studies looking at this have been in North America (Thompson et al 2007, van Wagtendonk et al 2012, Harris and Taylor 2017, with most only having one response fire, and occurring mostly in conifer forests. These studies have consistently found that fires reburn at the same or higher severity as the previous fire, supporting the idea of a positive feedback.…”
Section: Introductionmentioning
confidence: 99%